An Analysis on Figurative Language in Kitchen Nightmares TV Shows - Sa'adah, Hana; Rohana, Yogi (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Figurative language is a part of semantics, which has the function of making literary works or even daily conversation more interesting, attractive, and alive. TV-show is the one of electronic media which provides variety entertainment to the people. With the infrequency of linguistics research on TV shows, therefore the purpose of this study is to analyze the figurative language that is found on Kitchen Nightmares TV shows. The research was a content analysis, evaluating and interpreting data from targeted sources. The data was obtained from the official YouTube channel of Kitchen Nightmares. The data collection was done using the data sampling method. In data analysis, the researcher classified, identified, analyzed, and calculated the data to find the dominant types. In validating the data, analyst triangulation was done. After that, the top type related to the context to then draw a conclusion. The result showed that; (1) 4 metaphor, 8 metonymy, 8 hyperbole, 1 litotes, 21 irony, 8 simile, 10 personification. (2) the percentage of the types of figurative language were 7% metonym, 13% hyperbole, 2% litotes, 35% irony, 13% simile, and 17% personification. Hence, the dominant type of figurative language was irony, with the percentage 35% or 21 data. Furthermore, this study provided contribution in the education field to increase the students’ language skills.